FAMILY EDUCATION ACCORDING TO THE QUR’ANIC PERSPECTIVE - Wawan Wahyuddin (QATHRUNÂ, 2015)
This study aims (1) to describe law educates family members according to the Qur'anic perspective, (2) to describe the process of family education from the perspective of the Qur'an, and (3) to describe the family of educational material according to the perspective of the Qur'an. The problem of this study are (1) how the law educates family members according to the perspective of the Qur'an ?, (2) how the process of family education from the perspective of the Qur'an? And (3) how the theory of the family according to the perspective of the Qur'an? This study used a qualitative method of content analysis techniques. The Review is using tarbawi interpretation or education. The data source of this research are the verses of the Quran that that tells Abraham, Jacob, Imran, and Luqman Al-Hakim in educating families, interpretation of these verses, and stories about their life story. The conclusion of this study is the Qur'an discuss many prominent educators. The statement includes their success in educating families. Their success made them into servants and family choices as stated in the Qur'an Surah, Luqman, Imran and letters on the above. Therefore, in order to educate family the way or pattern that they do need to be followed by every chief of Muslim family.